2020
DOI: 10.1007/s12975-020-00821-0
|View full text |Cite
|
Sign up to set email alerts
|

Crossed Cerebellar Diaschisis Indicates Hemodynamic Compromise in Ischemic Stroke Patients

Abstract: Crossed cerebellar diaschisis (CCD) in internal carotid artery (ICA) stroke refers to attenuated blood flow and energy metabolism in the contralateral cerebellar hemisphere. CCD is associated with an interruption of cerebro-cerebellar tracts, but the precise mechanism is unknown. We hypothesized that in patients with ICA occlusions, CCD might indicate severe hemodynamic impairment in addition to tissue damage. Duplex sonography and clinical data from stroke patients with unilateral ICAO who underwent blood oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 25 publications
2
32
1
Order By: Relevance
“…By using a standardized region of interest, that is, the MCA territory, we found impaired BOLD‐CVR, prolonged MTT, and TTP as well as increased CBV in the ipsilateral (=affected) MCA territory in the CCD(+) group. These findings further confirm the observation that a vascular component of CCD may be present in patients with steno‐occlusive disease 3,5 …”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…By using a standardized region of interest, that is, the MCA territory, we found impaired BOLD‐CVR, prolonged MTT, and TTP as well as increased CBV in the ipsilateral (=affected) MCA territory in the CCD(+) group. These findings further confirm the observation that a vascular component of CCD may be present in patients with steno‐occlusive disease 3,5 …”
Section: Discussionsupporting
confidence: 87%
“…This means that in those patients the initial hemodynamic impairment and not the stroke severity influences CCD, most likely through metabolic downregulation. In our previous study we found more severe supratentorial BOLD‐CVR impairment in CCD patients 3 as well as a larger brain tissue volume exhibiting steal physiology and increased collateral compensatory flow 5 …”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations